CATCH COMPOSITION OF AMBAI NET IN KRUENG JAMBO AYE TIDAL CANAL FISHERIES, NORTH ACEH – INDONESIA - Muhammad Irham; Fitri Handayani; Ratna Mutia Aprilla; Anwar Deli (Research Center for Fisheries, 2021)
Increasing the amount of by-catch has become one of the causes of the decline in fish stocks that can threaten the sustainability of world fisheries. It may occur in small local brackish-water fisheries, especially in one of the tidal canals of North Aceh, i.e., Krueng Jambo Aye. Therefore, the investigation composition of the main catch and by-catch in a tidal channel of Krueng Jambo Aye is an essential indicator to describe the ecosystem impact by these fisheries. This study aims to determine the comparison of the composition of the main catches and by-catches, to determine the types of by-catches, and to identify the catch rate. The method used in this study is a field data collection and survey methods. The data analysis used was a capture rate analysis. The results showed that the main catches are more dominated by 72% while the by-catch by 28%. There are five species of by-catch with high economic value and nine species with low commercial value. The catch rate of the two catches are 0.42 kg per hour for the main catch and 0.16 kg per hour for the by-catch. It is expected that the results of this study can be used as necessary information to develop the fisheries improvement program in this area.